Gender Norms and Women's Decision to Work: Evidence from Japan - Núria Rodríguez-Planas; Ryuichi Tanaka (Institute of Labor Economics (IZA), 2021)
Using individual-level data from the National Family Research of Japan Survey (1999, 2004 and 2009) and exploiting variation in the share of individuals with non-traditional gender norms across birth-cohorts, survey year, education, and prefecture, we find that an increase in the share of individuals with non-traditional beliefs by one standard deviation is associated with an increase in Japanese women's decision to work by 0.016 percentage points, the equivalent of an increase of 3.4% standard deviation. Our measure of non-traditional gender norms is the share of women who disagree with the statement "men should work outside and women should look after the family". As we conduct a battery of sensitivity analyses and placebo tests, our findings suggest an impact of non- traditional norms on Japanese women's decision to work full-time.
Keywords: J16; J22; Z13; 330; gender norms; women's decision to work; culture